Biosemiotics of Water in the Quran Surah Al-Anbiya' Verse 30 - Chaer, Hasanuddin; Sirulhaq, Ahmad; Rasyad, Abdu; Malik, Djamil Abdurachman (MOZAIK HUMANIORA, 2023)
Biosemiotics delves into the examination of meaning, communication, and signs within every living microorganism. This research endeavors to interpret the Qur'anic passage "wajalna minal maa' kulla syai'in hayyin," which translates to "we make water molecules as a source of signs of life." Its objective is to discern and elucidate the microbial presence within the water molecule by scrutinizing the term Ø§Ù„Ù’Ù…ÙŽØ§Û¤Ø¡Ù 'water' in surah al-Anbiya' verse 30 through a scientific lens, thus acting as a juncture between biology and semiotics. Employing a qualitative approach and content analysis as the methodological framework, the research encompasses stages of data collection, processing, interpretation, and presentation of findings. The study adopts Saussure's Dyadic Model as the theoretical foundation to construe the meaning of semiotic signs of water from a biological perspective. The outcomes of the research underscore the existence of microorganisms within the water molecule, signifying the evolution of life, thereby enabling a reconfiguration of the term 'alma'' into the realm of semiotic signs through the synthesis of ideas in studies of semiotic-biology. Biosemiotics perceives the evolution of life and semiotic systems as distinct yet interlinked studies, both striving to reconstruct the same underlying meaning.